PENGARUH FAKTOR BUDAYA, SOSIAL, KARAKTERISTIK PRIBADI TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI TOKOPEDIA - ILHAMALIMY, RIDHO RAFQI; CHASANAH, AFRIDA NUR; KARTIKANINGRUM, SARI (Universitas Mahasaraswati K. Mataram, 2024)
The development of the times has given rise to a new type of media called the internet. Starting from the convenience provided by the internet to carrying out daily activities such as searching for information, communicating and shopping. Online purchases (Online Shop), are shopping activities carried out via the internet. In the business world, the higher the competition, the higher the marketing strategies implemented by a number of industries and companies at the global level. The aim of this research is to determine the partial influence of cultural, social and personal characteristics factors on purchasing decisions on the Tokopedia application. Descriptive quantitative research method with a sample size of 97 people. Data analysis was carried out using SPSS Statistical Program for Social Sciences 2.7. The results of the research found that cultural factors partially had a positive and significant influence on purchasing decisions at Tokopedia, then partially social factors had a positive and significant influence on purchasing decisions at Tokopedia, and partially personal characteristic factors had a positive and significant influence on purchasing decisions. on Tokopedia